A feedback linearisation algorithm for single-track models with structural stability properties. (November 2022) - Bascetta, Luca; Farina, Marcello; Gabrielli, Alessandro; Matteucci, Matteo
Abstract: To support the design of trajectory tracking controllers, by way of linear tools, for vehicles characterised by nonholonomic constraints, this paper proposes a feedback linearising law for single-track dynamic models. The main characteristics of this algorithm are its simplicity, its independence from any vehicle model parameter, apart from the position of the center of mass, and its robustness. A numerical bifurcation analysis demonstrates that, for physically meaningful values of the center of mass deviation, the equilibrium is structurally asymptotically stable. Experimental results, concerning the linearising law and its application as inner loop of a trajectory tracking controller, are also presented, confirming the efficacy of the proposal. Highlights: A feedback linearising law for single-track dynamic models. Simple and independent of any vehicle parameter, except center of gravity position. Guarantees robust asymptotic stability in the presence of uncertainties.